EVENING CULINARY TOURISM: THE PUBLICITY OF MERDEKA WALK MEDAN - Faustyna Faustyna (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Publicity is very important to evening culinary tourism information in Merdeka Walk Medan, North Sumatra to increase the number of local and foreign tourists who visit and enjoy the evening atmosphere and menus. A Public Relations Officer has the means to carry out his/her duties such as a publicity agent. Publicity is carried out to the public, and the public is needed to inform about the products or services offered by government agencies, organizations, companies, or individual to attract local and foreign tourists to visit the aforementioned evening culinary tourism. The method used in this paper is a qualitative; focusing mainly on the role of Public Relations Officer who uses mass media to publish events held at Merdeka Walk and also publishes a variety of menu that reflects the taste of the region and its ethnicity. Internet-based social media plays an important role in publicity. Through social media, people can be made aware of the beauty and convenience of culinary locations at Merdeka Walk. Social media, thus, results in boosting the popularity of this culinary tourism, and it shows that the effects of the publication have been felt.